(untitled) (The Pretoria Student Law Review, 2023)
Modernity significantly influences global action regarding social, political, and economic justice and liberation. Because of this, its flawed origins cannot simply be ignored. This article explains the development and current conception of economic, social and political modernity and shows how non-Western thought is excluded from these spheres. The article focuses on problematising he recent construction of modernity by showing how modernity is founded on Western ideals. Additionally, this article tracks the spread and universalisation of modernity by cruel and illegitimate means like colonialism and the othering of indigenous peoples. All these form the basis for an arguments that there must be a substantial reconstruction of the concept of modernity, and TWAIL’s relationship with international law is offered as inspiration for such a reconstruction.